A theoretical intellectual capital model applied to cities - José Luis Alfaro Navarro; Víctor Raúl López Ruiz; Domingo Nevado Pena (Amfiteatru Economic)
New Management Information Systems (MIS) are necessary at local level as the main source of wealth creation. Therefore, tools and approaches that provide a full future vision of any organization should be a strategic priority for economic development. In this line, cities are “centers of knowledge and sources of growth and innovation” and integrated urban development policies are necessary. These policies support communication networks and optimize location structures as strategies that provide opportunities for social and democratic participation for the citizens. This paper proposes a theoretical model to measure and evaluate the cities intellectual capital that allows determine what we must take into account to make cities a source of wealth, prosperity, welfare and future growth. Furthermore, local intellectual capital provides a long run vision. Thus, in this paper we develop and explain how to implement a model to estimate intellectual capital in cities. In this sense, our proposal is to provide a model for measuring and managing intellectual capital using socio-economic indicators for cities. These indicators offer a long term picture supported by a comprehensive strategy for those who occupy the local space, infrastructure for implementation and management of the environment for its development.